2010
DOI: 10.4103/0973-1296.66944
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of extracts from Tamarindus indica L. leaves

Abstract: Tamarindus indica L. leaves are reported worldwide as antibacterial and antifungal agents; however, this observation is not completely accurate in the case of Cuba. In this article, decoctions from fresh and sun dried leaves, as well as fluid extracts prepared with 30 and 70% ethanol-water and the pure essential oil from tamarind leaves were microbiologically tested against Bacillus subtilis, Enterococcus faecalis, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, Pseudomona aeruginosa and Candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 13 publications
5
43
1
3
Order By: Relevance
“…These observations are in accordance with the earlier observations reported by and they also reported that Gramnegative organisms were less susceptible to the herbal extracts than Gram-positive isolates [3,5]. It may possibly be due to the presence of high lipid content in the cell walls of Gram negative bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…These observations are in accordance with the earlier observations reported by and they also reported that Gramnegative organisms were less susceptible to the herbal extracts than Gram-positive isolates [3,5]. It may possibly be due to the presence of high lipid content in the cell walls of Gram negative bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…McLaughlin, Daniels, & Yadav, 2013;Hayek & Ibrahim, 2012;Nisa et al, 2013). Other work has also reported the resistance of S. marcescens and P. aeruginosa bacteria to plant extracts (Escalona-Arranz et al, 2010;Koolen et al, 2013). The MIC of extracts against test organisms ranged from 0.6 to 10 mg/mL with B. pilosa showing higher activity against Staphylococcus epidermidis at 0.6 mg/mL (Figure 1).…”
Section: Antimicrobial Activity Of M Oleifera and B Pilosa Leaf Extmentioning
confidence: 90%
“…These properties may be attributable to the presence in the plant of various phytochemicals with, among others, antibacterial, antifungal, antiviral, antiparasitic, anti-inflammatory, and antioxidant properties [191,192,193,194]. T. indica leaves contain various polyphenols and flavonoids with wound healing-stimulating properties [195,196], the seeds contain the hemicellulose xyloglucan which can protect the skin from the damaging effects of ultraviolet radiation [197], and the seed oil contains abundant amounts of linoleic acid and oleic acid [194].…”
Section: Tamarindus Indica Lmentioning
confidence: 99%